Pengaruh Perangkat Lunak E-Commercce Terhadap Bisnis di Masa Pandemi Covid-19 - Herdian Nur Rahman; Nadira Paramita; Rapika Hannum; Nurbaiti (Melati Institute, 2022)
The use of information systems (IS) and information technology (IT) by business people is an interesting thing to know. These systems and technologies are mentioned as drivers that play an important role in the sustainable growth of a business organization. One of the components of AIS is software. Software is a program or collection of programs the tenable hardware to process data. Besides AIS, e-commerce is also a form of information system. Electronic commerce (e-commerce) describes the process of buying, selling, transferring, or exchanging products, services, or information through networks, including the internet. Behind the pandemic, there are several e-commerce companies in Indonesia that have recorded an increase in turnover, although People practice physical distancing in the midst of the Covid-19 outbreak. This article uses a qualitative approach. The research method uses a literature review related to the trend of increasing business E-commerce software due to the covid-19 pandemic. Based on the analysis of research results and discussions that have been described, it can be concluded that software has a significant positive effect on online business and on economic development performance during the pandemic.